Estonian energy supply strategy assessment for 2035 and its vulnerability to climate driven shocks. Issue 2 (8th September 2015) - Lehtveer, Mariliis; Pelakauskas, Martynas; Ipbüker, Cagatay; Howells, Mark; Rogner, H‐Holger; Das, Anjana; Toomet, Ott‐Siim; Tkaczyk, Alan H.
Abstract : Estonia is a relatively small country with a limited supply of indigenous energy resources mainly consisting of oil shale, wood, and peat. Estonia is also the only country in Europe with a dominant electricity production by burning oil shale. Around 90% of the overall electric energy production in Estonia comes from the Narva Power Plants. This presents great challenges and problems due to massive emissions of greenhouse gases into the atmosphere as well as radiological impact on the environment. Therefore, the current energy supply strategy can be considered hazardous and an unpopular choice for future energy system planning. In this article, we analyze the current energy policy as well as inclusion of new strategies to produce electricity for Estonia for a target year of 2035. We use a computer model Model for Supply Strategy Alternatives and their General Environmental Impacts (MESSAGE) to provide optimization and aim in helping the policymakers in the Estonian decision making process. We also add a specific case in the MESSAGE model to examine the ability of the current electricity supply strategy to handle climate related shocks with a special focus on cold weather in two plausible cases; single cold winter and prolonged cold winter. Results indicate that unexpected demand shocks may cause serious losses in gross domestic product (GDP). Therefore, the authors come to the conclusion that extra capacity is highly recommendable for a number of reasons. We also find that nuclear power becomes economically preferable to oil shale with a CO2 tax of €20/t. Yet moving toward nuclear or other low CO2 alternatives presents certain challenges. © 2015 American Institute of Chemical Engineers Environ Prog, 35: 469–478, 2016